Analysis of Social Commerce Success Using the Expectation Confirmation Model (ECM) Method - Wanti, Linda Perdana; Prihantoro, Andesita (Journal of Multimedia Trend and Technology, 2024)
The rapid development of social commerce has changed the way consumers shop and interact with brands. However, the success of social commerce platforms cannot be separated from a deep understanding of the factors that influence consumer satisfaction and purchase intentions. This study aims to analyze the success of social commerce using the Expectation Confirmation Model (ECM) method. ECM is a model that explains that consumer satisfaction is influenced by the confirmation of their expectations of a product or service. This study identifies the main problems in social commerce, namely consumer uncertainty about product quality, transaction security, and shopping experiences that meet expectations. The research method used is a quantitative approach with a survey of consumers who have shopped through social commerce platforms. Data were analyzed using descriptive and inferential statistical techniques to test the research hypothesis. The results of the study showed that confirmation of consumer expectations about product quality, transaction security, and ease of use of the social commerce platform had a positive effect on their satisfaction. In addition, consumer satisfaction also influenced their repurchase intentions on the platform. Based on these findings, this study offers solutions for social commerce managers to increase the success of their platforms. These solutions include providing clear and accurate product information, ensuring transaction security, and improving an easy and enjoyable shopping experience.